Design of Dielectric Lens Loaded Double Ridged Horn Antenna for Millimetre Wave Application - Demirel, Salih; Caliskan, Alper; Mersin, Mucahid T.; Turk, Ahmet S.; Belen, Mehmet A.; Mahouti, Peyman (IEEE, 2016)
In this paper, designs of Dielectric Lens Loaded Double Ridged Horn Antenna for Millimetre Wave Applications is investigated. Firstly a double ridged horn antenna is designed and simulated in CST environment. After that, 2 dielectric lens architecture are designed and placed at the aperture of the antenna. It is seen that by placing spherical shaped dielectric lens, it is possible to achieve improvement in return loss and far-field gain of the antennas design in a 20-40 GHz bandwidth.
Keywords: dielectric loaded antenna; millimetre band; ridged horn antenna; Engineering; Telecommunications